International Classification of Functioning, Disability and Health (ICF) and correlation between disability and finance assets in chronic stroke patients - Marotta, Nicola; Ammendolia, Antonio; Marinaro, Cinzia; Demeco, Andrea; Moggio, Lucrezia; Costantino, Cosimo (Acta Biomedica Atenei Parmensis, 2020)
Background. Stroke is the third cause of long term disability worldwide and its rehabilitation program must to have into account all aspects of disability. International research and politics increasingly study the relationship between disability and the direct costs associated with living with a disability.Objective. Using the ICF, this article provides a correlation between financial assets and disability in participation and activities, in a context such as the Italian one where there is a twenty-year decentralization of the national health systemMethods. At the University of Catanzaro, in southern Italy, n=130 ICF checklists of stroke patients were analyzed at 6 months from the end of the rehabilitation treatment. Financial assets domains in environment and nine domains in participation and activities were correlated, in order to evaluate the relationship between familiar economic condition and disability. Results. Pearson's r test (t = -6.6515, df = 25, p-value